2010
DOI: 10.1063/1.3432571
|View full text |Cite
|
Sign up to set email alerts
|

Study of active surface defects in Ti doped ZnO nanoparticles

Abstract: The effects of surface defect (oxygen vacancies) on the electronic structure and photoluminance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…4b). This particle size-dependent shift in the optical band gap is found to be consistent with the literature [22]. We also conducted a detailed study on the role of particle size and concentration for the antibacterial activity of ZnO nanoparticles against Staphylococcus aureus.…”
Section: Resultssupporting
confidence: 89%
“…4b). This particle size-dependent shift in the optical band gap is found to be consistent with the literature [22]. We also conducted a detailed study on the role of particle size and concentration for the antibacterial activity of ZnO nanoparticles against Staphylococcus aureus.…”
Section: Resultssupporting
confidence: 89%
“…It has been found that the intensity of DLE increases (Figure d) with increasing inclusion of Ti in the ZnO thin film up to 1%, since DLE depends on the density of free carriers and defects generated by the oxygen vacancies in the ZnO lattice. Here, the inclusion of Ti impurities could be the cause of the increase in the green light (at ∼560 nm) peak intensity, as reported by Chang et al As reported by Naeem et al, Ti impurities in the TZO-1 sample can increase the intensity of the green emission peak and increase the ionized oxygen vacancy in the ZnO lattice. However, at the high Ti doping concentration (TZO-3 and TZO-5), the PL intensity is observed to be slightly low compared to the TZO-1 sample, which may be ascribed to the increment in O i or Zn i defects.…”
Section: Resultssupporting
confidence: 57%
“…All the PL spectra have two emitting bands including a weak emission band in UV region (365 nm) and a strong emission band in visible region (centered at 550 nm). The UV emission band originates from the direct recombination of the free excitons through an exciton-exciton collision process, while the green emission peaks are due to radial recombination of the photo-generated hole with the electrons that belongs to the singly ionized oxygen vacancies [43][44][45]. When the ZnO:Co nanorods are annealed at different temperatures in the presence of O 2 , oxygen vacancy at the surface of ZnO is removed which results in the decrease of green emission.…”
Section: Gas Response and I-v Properties Of Zno:co Nanorodsmentioning
confidence: 98%